Case report: Be alert to herpes zoster after total knee arthroplasty - Wei, Zhanqi; Weng, Xisheng (Frontiers in Surgery, 2023)
An 88-year-old woman started complaining of severe pain at the right knee and above at three weeks after right total knee arthroplasty (TKA). The empirical treatment cannot effectively control the progress of pain. The lesion was eventually diagnosed to be due to herpes zoster (HZ). The finding of HZ was unexpected in this case, because HZ is extremely rare in patients after TKA.